ALIMENTARY-DEPENDENT DISEASES IN MODERN CHILDREN: THE CORRECTION WAYS - A. S. Polyashova (Вопросы современной педиатрии)
Rational diet, age-appropriate for the growing organism needs, provides normal physical and mental development and preventsalimentary-dependent diseases at every age stage. Deficiency of vitamins, minerals and other essential nutrients, gradually progressing against the background of imbalanced diet, leads to development of multisystem disorder, which then can become chronic. It is important that paediatricians pay great attention to supplementation in children’s nourishment of ω-3 polyunsaturated fatty acids, which have significant influence on visual apparatus, intellectual development and different organs and systems functions. The easing of the adaptation syndrome at the beginning of school education and supplementation of attention deficit can be achieved by the courses of vitamin complexes PIKOVIT, which demonstrated high efficiency and safety even in allergic disorders and are recommended by the specialists of Moscow Scientific Centre of Children Health.